An introduction to Shakespeare : the dramatist in his context (Mac millan, 1996)
Peter Hyland provides a highly readable account of the historical, social and political pressures of Shakespeare's England and the material conditions under which his plays were written, including a comprehensive description of the development and status of the theatrical profession.